Penetrating Trauma: Representing Rape in the Historical Drama Series Feast of the Uninvited. Issue 4 (2nd October 2018) - Jansen van Vuuren, Anna-Marie
ABSTRACT: In the drama series Feast of the Uninvited, director Katinka Heyns portrays some of the pain and trauma experienced by families during the South African War (also known as the Anglo-Boer War). Within the storyline, the character of Magrieta Van Wyk is raped by a Boer man. This is one of the first physical "on screen" representations of rape in an Afrikaans television production, and because of this, the MNET series ignited a lot of controversy among audiences. Through this representation, Heyns challenges the traditional notion of the "pure and heroic" Boer hero that has become a well-known archetype within films and drama series set against this time period. While witnessing Magrieta's rape on screen, we only later find out that the black housemaid Siena was also raped in a concentration camp reserved for black women and children. It is one of the first audio-visual case studies that mention black women's suffering during this war, but it is still only given a brief glance. The author concludes that the collaborative effort of Heyns and cinematographer Koos Roets, combined with powerful performances, recreates the harshness of the South African War, and more specifically the traumatic experiences of women during this war.